Desenvolvimento front-end: módulo aluno do software educacional Loop Academic - Sá, Gabriel Caldas Barros e (Universidade Federal Rural do Semi-Árido, 2019)
A large amount of students in computer and technology areas face many difficulties in introductory programming subjects, and this reflects on the lack of preparation to enter in the job market. To reduce this problem, which also occurs in many others studying areas, Educational Softwares have been used to assist both the students and the teachers in the teaching-learning process. With this in mind, this research focuses on the development of the Client Side and the main functionalities of the Student module of the educational web software named Loop Academic, built using HTML5, CSS, JavaScript and other tools, whose targets are the students of the subjects that involve introductory computer programming. Therefore, the methodology applied consists in the choice of the web development tools, study of the already existing prototype of the Student module, the selection of the main functionalities and, at last, coding the front-end, resulting in a static system that will serve as a base for future works that aim to develop the other components of the system.
Keywords: Desenvolvimento web; Software; Programação; Front-end; Informática na educação; Web development; Educational software; Programming; Information technology on education; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA